Antimicrobial Activity of EndemicHypericum havvaefrom Turkey - DULGER, BASARAN; HACIOGLU, NURCIHAN; DULGER, GORKEM (Asian Journal of Chemistry, 2010)
n-Hexane, ethyl acetate, ethanol and aqueous extracts of Hypericum havvae A.Guner (Hyperiaceae) were tested for their antimicrobial activity against Escherichia coli ATCC 11230, Enterobacter aerogenes ATCC 13048, Alcaligenes faecalis CCM 3763, Salmonella typhimurium CCM 5445, Citrobacter freundii ATCC 8090, Staphylococcus aureus 6538P, Bacillus cereus ATCC 7064, Bacillus subtilis ATCC 6633, Bacillus brevis ATCC 9999, Pseudomonas aeruginosa ATCC 27583, Proteus vulgaris ATCC 8427, Micrococcus luteus CCM 169, Micrococcus flavus ATCC 14452, Candida albicans ATCC 10231, Rhodotorula rubra DSM 70403 and Kluyveromyces fragilis ATCC 8608. While extracts of the plant have shown strong antimicrobial activity against the tested bacteria, they have weak activity against the tested yeast cultures.